1331. Learning Experiences Within Infectious Diseases Pharmacy Residency Programs Demonstrate High Degrees of Consistency. (26th November 2018) - Cho, Jonathan; Crotty, Matthew; Kufel, Wesley; Chahine, Elias; Sofjan, Amelia; Gallagher, Jason; Estrada, Sandy
Abstract: Background: Pharmacists with residency training in infectious diseases (ID) optimize antimicrobial therapy outcomes in patients and support antimicrobial stewardship programs. The purpose of this study was to describe the learning experiences currently being offered in post-graduate year-2 (PGY-2) ID pharmacy residency programs. Methods: A 19-item, cross-sectional, multi-centered, electronic survey was distributed via e-mail to pharmacy residency program directors (RPDs) of all 101 accredited and nonaccredited PGY-2 ID residency programs in the United States. Programs were identified via the ASHP, ACCP, and SIDP residency directories. Program characteristics inquired via the survey included required and elective learning experiences, research and teaching opportunities, and ID-related committee involvement. Results: Survey responses were collected from 71 RPDs (70.3%). Most programs were associated with an academic medical center (64.8%), focused primarily in adult ID (97.2%), and accepted one resident per year (91.6%). Forty-eight (67.6%) institutions also offered an ID physician fellowship program. Microbiology laboratory, adult antimicrobial stewardship (AS), and adult ID consult learning experiences were required in 98.6% of residency programs. Only 28.2% of responding programs required pediatric AS and pediatric ID consult rotations. Greater than 90% of RPDs reported that the resident managed bone and joint, lower respiratory tract, sepsis, urologic, and skin and soft-tissue infections at least once weekly. Travel medicine, parasitic infections, hepatitis B, and hepatitis C were either rarely or never encountered by the resident in 77.5%, 76%, 66.2%, and 50.7% programs, respectively. Residents were frequently involved in AS committees (97.2%), pharmacokinetic dosing of antimicrobials (83.1%), precepting pharmacy trainees (80.3%), and performing research projects (91.5%). Conclusion: PGY-2 ID pharmacy residency programs in the United States demonstrated consistency in required adult ID consult, antimicrobial management activities, AS committee service, and teaching and research opportunities. Pediatric experiences were less common. PGY-2 ID residency programs prepare pharmacists to become antimicrobial stewards, particularly in adult patients. Disclosures: J. Cho, Allergan: Speaker's Bureau, Speaker honorarium. M. Crotty, Theravance and Nabriva: Consultant, Consulting fee. E. Chahine, Merck: Speaker's Bureau, Speaker honorarium. Allergan: Scientific Advisor, Consulting fee. J. Gallagher, Allergan, Astellas, Merck, and Melinta: Speaker's Bureau, Speaker honorarium. Achaogen, Allergan, Astellas, Cempra, Cidara, CutisPharma, Merck, Paratek, Shionogi, Tetraphase, Theravance, and The Medicines Company: Consultant, Consulting fee. Merck: Grant Investigator, Research grant. S. Estrada, Allergan, Astellas, Merck, T2Biosystems and The Medicines Company: Speaker's Bureau, Speaker honorarium. The Medicines Company and Theravance: Grant Investigator, Research grant. Astellas, CutisPharma, Theravance, and The Medicines Company: Consultant, Consulting fee.